ORP2 couples LDL‐cholesterol transport to FAK activation by endosomal cholesterol/PI(4, 5)P2 exchange. (14th June 2021) - Takahashi, Kohta; Kanerva, Kristiina; Vanharanta, Lauri; Almeida‐Souza, Leonardo; Lietha, Daniel; Olkkonen, Vesa M; Ikonen, Elina
Abstract: Low‐density lipoprotein (LDL)‐cholesterol delivery from late endosomes to the plasma membrane regulates focal adhesion dynamics and cell migration, but the mechanisms controlling it are poorly characterized. Here, we employed auxin‐inducible rapid degradation of oxysterol‐binding protein‐related protein 2 (ORP2/OSBPL2) to show that endogenous ORP2 mediates the transfer of LDL‐derived cholesterol from late endosomes to focal adhesion kinase (FAK)‐/integrin‐positive recycling endosomes in human cells. In vitro, cholesterol enhances membrane association of FAK to PI(4, 5)P2 ‐containing lipid bilayers. In cells, ORP2 stimulates FAK activation and PI(4, 5)P2 generation in endomembranes, enhancing cell adhesion. Moreover, ORP2 increases PI(4, 5)P2 in NPC1‐containing late endosomes in a FAK‐dependent manner, controlling their tubulovesicular trafficking. Together, these results provide evidence that ORP2 controls FAK activation and LDL‐cholesterol plasma membrane delivery by promoting bidirectional cholesterol/PI(4, 5)P2 exchange between late and recycling endosomes. Synopsis: How LDL‐cholesterol is delivered from late endosomes to the plasma membrane and enhances cell motility is unknown. Here, this is found to depend on ORP2‐mediated lipid exchange between late endosomes and focal adhesion kinase (FAK)‐positive recycling endosomes promoting FAK activation. Loss of ORP2 abrogates LDL‐cholesterol delivery from late to recycling endosomes. LDL‐cholesterol activates FAK pending ORP2‐mediated cholesterol transfer. FAK activity promotes PI(4, 5)P2 generation in endosomes, fueling the delivery of LDL‐cholesterol to the plasma membrane. ORP2 controls endomembrane distribution of PI(4, 5)P2 and tubulation of NPC1‐positive endosomes. Abstract : Cholesterol effects on cell motility depend on ORP2‐mediated lipid transfer from late endosomes to focal adhesion kinase‐/integrin‐positive recycling endosomes.